2000
DOI: 10.1055/s-2007-978596
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of L-Carnitine on Prepubertal Rat Sertoli Cells

Abstract: The role of carnitine on Sertoli cell metabolism was investigated. Carnitine effects on Sertoli cell lipid metabolism were evaluated by measuring the intracellular levels of non-esterified fatty acids (NEFA) and ketone bodies. The concentration of NEFA in Sertoli cell cultured in the presence of carnitine is significantly reduced as compared to control, while, no significant changes were observed in the concentration of ketone bodies. The functional parameters evaluated to assess the influence of carnitine on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 5 publications
3
24
0
1
Order By: Relevance
“…In this study, it is likely that part of the protective action provided by carnitine to the seminiferous epithelium was mediated by Sertoli cells, by maintaining the blood-testis barrier function, as the Sertoli cells express OCTN2, the Carnitine/ Organic Cation Transporter 2, commonly found in blood-tissue barriers (Kobayashi et al 2005). Indeed, Palmero et al (2000) demonstrated that carnitine acts directly on the Sertoli cells in vitro, improving their physiology and, consequently, germ cell development and maturation. Nevertheless, this issue still deserves further investigation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this study, it is likely that part of the protective action provided by carnitine to the seminiferous epithelium was mediated by Sertoli cells, by maintaining the blood-testis barrier function, as the Sertoli cells express OCTN2, the Carnitine/ Organic Cation Transporter 2, commonly found in blood-tissue barriers (Kobayashi et al 2005). Indeed, Palmero et al (2000) demonstrated that carnitine acts directly on the Sertoli cells in vitro, improving their physiology and, consequently, germ cell development and maturation. Nevertheless, this issue still deserves further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…Our results indicate that, indeed, doxorubicin causes damage to sperm DNA and that carnitine anyhow maintains its integrity. Palmero et al (2000) also showed that exogenous carnitine might act as a cellular protector through the stimulation of DNA repair by serving as an extra source of acetyl group to the coenzyme A, by increasing cellular energy metabolism and favoring DNA repair and germ cell development. In addition, carnitine may operate through a mechanism likely involved in the inhibition of ceramides production; such characteristic reasserts carnitine as a promising cytoprotector, capable of avoiding the cellular depletion caused by chemotherapy (Andrieu-Abadie et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5b), suggesting that carnitine can be passed from the blood circulation to Sertoli cells, as well as germ cells. This speculation was supported by the findings that oxidation of fatty acids is likely to be the major energy source for Sertoli cells (Jutte et al 1985) and that L-carnitine treatment significantly reduced non-esterified fatty acids in cultured rat Sertoli cells (Palmero et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Because of its antioxidant properties, carnitine has been used in the treatment of male infertility (Vicari et al 2002;Lenzi et al 2003) and as a cytoprotective substance against the toxicity of drugs such as alcohol and bleomycin (Arafa and Sayed-Ahmed 2003;Demirdag et al 2004;Sayed-Ahmed et al 2004). Moreover, Palmero et al (2000) have demonstrated that carnitine acts directly on the Sertoli cells in vitro, improving their physiology and, consequently, the development of the germ cells. In view of the therapeutic, antioxidant, and cytoprotective properties of carnitine in other tissues, we have investigated whether carnitine protects rat testes against etoposide and, thus, improves fertility in adulthood.…”
Section: Introductionmentioning
confidence: 99%